EFL UNIVERSITY STUDENTS’ MOTIVATION, COGNITIVE LOAD, AND SATISFACTION WITH USING GENAI FOR ENGLISH LEARNING - Lee, Yong Jik; Otani, Masashi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This study examined how the integration of GenAI affects students’ writing learning experiences, examining factors related to motivation, cognitive load, and satisfaction. Data collection involved an end-of-semester survey assessing these three dimensions in the context of AI-integrated writing pedagogy. The results indicate that EFL students generally hold positive perceptions of GenAI’s value and utility for writing development, expressing interest in learning more about AI-assisted writing tools and recognizing their practical importance for academic writing tasks. Students’ motivation was high regarding the relevance and engaging nature of GenAI in writing contexts. The analysis of cognitive load showed moderate levels of mental effort when integrating GenAI into writing processes. The satisfaction data underscore the writing course’s success in fostering enthusiasm, engagement, and practical application of AI writing knowledge, with participants rating the AI-integrated writing course favorably. However, areas such as knowledge retention of AI writing strategies and clarity of understanding AI’s role in writing suggest opportunities for improvement. These findings highlight the potential of GenAI integration in EFL writing instruction, while also identifying specific areas for enhancing writing-focused learner outcomes.